Importing American racial reasoning to social science research in Sweden (Sociologisk Forskning, 2020)
How does one research racial categorizations and exclusion while remaining sensitive to context? How does one engage the social reality of racial categorizations and the history of racialized exclusions without falling into the trap of race essentialism? These concerns prompt debate about, and also resistance to, examining race in Swedish social science. In this article, Voyer and Lund offer American racial reasoning as one possible approach to researching race in the Swedish context. American racial reasoning means being attentive to how power and the processes of social inequality operate through categories of racial and ethnic difference, and also seeing the path to greater equality in the embrace of those categories. American racial reasoning is a valuable research tool that uncovers dynamics of social inequality and possibilities for social justice that are otherwise difficult to grasp. Taking up the topic of immigration in Sweden, Voyer and Lund demonstrate the analytical value of American racial reasoning for understanding persistent social inequality and exclusion even when explicit racial categories are not in wide use in everyday life.